Centipede systematics: progress and problems* - Edgecombe, Gregory D. (Zootaxa, 2007)
Breakthroughs in centipede systematics over the past 25 years have included: a stable morphology-based cladogram for ordinal interrelationships that is largely congruent with well-sampled nuclear ribosomal genes; the discovery of mid Palaeozoic crown-group fossils, including Silurian-Devonian stem-group Scutigeromorpha and an extinct order in the Middle Devonian; and, a web-based catalogue of all centipede species globally. Challenges include species delimitation in several groups, conflict between different kinds of molecular data (nuclear coding genes versus ribosomal genes), the inter-familial relationships and classification of the Geophilomorpha in particular, and effecting a synthesis between microanatomical studies of selected ‘model’ species and dense taxonomic sampling in numerical phylogenetic analyses.